This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Small typo: The 'curious formula' should be k = 1 ∑ n k 3 = ( k = 1 ∑ n k ) 2 not k = 1 ∑ n k 3 = ( k = 1 ∑ n k 2 ) 2
Problem Loading...
Note Loading...
Set Loading...
We have the curious formula k = 1 ∑ n k 3 = ( k = 1 ∑ n k ) 2 = ( 2 n ( n + 1 ) ) 2 . For n = 9 1 this gives 1 7 5 2 2 5 9 6 .
We can prove this by induction, which is cheating a bit since we pull the formula "out of thin air."
Or we can use the standard approach: k 4 − ( k − 1 ) 4 = 4 k 3 − 6 k 2 + 4 k − 1 Adding these up for k = 1 . . . n , we find n 4 = 4 k = 1 ∑ n k 3 − 6 k = 1 ∑ n k 2 + 4 k = 1 ∑ n k − n Solving for ∑ k 3 and using the familiar formulas for ∑ k 2 and ∑ k , we end up with k = 1 ∑ n k 3 = 4 n 4 + n ( n + 1 ) ( 2 n + 1 ) − 2 n ( n + 1 ) + n = ( 2 n ( n + 1 ) ) 2 after a bit of routine algebra.
There must be a more direct way to derive this formula...